2021
DOI: 10.3390/pharmaceutics14010045
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Additive Effect of Silymarin in Metformin Therapy of Liver Steatosis in a Pre-Diabetic Model

Abstract: The combination of plant-derived compounds with anti-diabetic agents to manage hepatic steatosis closely associated with diabetes mellitus may be a new therapeutic approach. Silymarin, a complex of bioactive substances extracted from Silybum marianum, evinces an antioxidative, anti-inflammatory, and hepatoprotective activity. In this study, we investigated whether metformin (300 mg/kg/day for four weeks) supplemented with micronized silymarin (600 mg/kg/day) would be effective in mitigating fatty liver disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…49 It has been reported that SREBP1, a member of the SREBP family, is primarily involved in regulating cholesterol, fatty acids, and triglycerides and is considered to be responsible for controlling lipid metabolism homeostasis in animals. 50 Increasing evidence has demonstrated that some bioactive substances, such as silymarin, 51 ginsenoside Rg1, 52 and naringin, 53 can alleviate HFD-induced hepatic steatosis by inhibiting the expression of PPARγ and SREBP-1c in the liver. Similar results were found in our study: the GAA supplementation noticeably reduced the levels of PPARγ and SREBP-1c in HFD-fed mice, implying that GAA mitigates HFD-induced hepatic steatosis and lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…49 It has been reported that SREBP1, a member of the SREBP family, is primarily involved in regulating cholesterol, fatty acids, and triglycerides and is considered to be responsible for controlling lipid metabolism homeostasis in animals. 50 Increasing evidence has demonstrated that some bioactive substances, such as silymarin, 51 ginsenoside Rg1, 52 and naringin, 53 can alleviate HFD-induced hepatic steatosis by inhibiting the expression of PPARγ and SREBP-1c in the liver. Similar results were found in our study: the GAA supplementation noticeably reduced the levels of PPARγ and SREBP-1c in HFD-fed mice, implying that GAA mitigates HFD-induced hepatic steatosis and lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin is one of the most important medicinal plant extracts obtained from milk thistle (Rainone, 2005) that, by improving inflammatory factors and increasing antioxidant capacity, can improve cellular damage in the liver, prevent and improve fibrosis and cirrhosis, and reduce liver damage caused by some drugs (Ali et al, 2018; Fehér & Lengyel, 2012; Kheiripour et al, 2019; Tao et al, 2019; Vargas‐Mendoza et al, 2014). Several studies have reported the therapeutic effects of silymarin in liver diseases, including fatty liver disease, hepatic steatosis, liver fibrosis, and cirrhosis (Abenavoli et al, 2018; Cacciapuoti et al, 2013; Chen et al, 2012; Colica et al, 2017; Famouri et al, 2016; Fehér & Lengyel, 2012; Hüttl et al, 2021; Kalopitas et al, 2021; Ni & Wang, 2016; Solhi et al, 2014; Tsai et al, 2008; Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[ 161 ] At the molecular level, the expression of transcription factors involved in lipid metabolism, such as PPARγ, and PPARα in the liver, has been postulated by Silymarin, suggesting its beneficial effects in the treatment of fatty liver. [ 162 ]…”
Section: Therapeutic Intervention For Hyperglycemiamentioning
confidence: 99%